1999
DOI: 10.1038/sj.bmt.1701804
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of feasibility of myeloablative therapy and autologous peripheral stem cell (PBSC) transplantation in the elderly: an interim report

Abstract: Summary:An interim report evaluating the feasibility of myeloablative therapy followed by peripheral blood stem cell (PBSC) autotransplant in patients aged Ͼ60 years is presented. In the last 2 years 19 patients Ͼ60 years old with several oncological conditions, mostly hematological, underwent PBSC autotransplant either as salvage therapy following relapse or resistance to conventional treatment, or as consolidating therapy as a part of a well defined protocol. There were 13 males and six females; the mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
(32 reference statements)
1
19
1
Order By: Relevance
“…Stamatoullas et al 16 transplanted two patients older than 65 years. Our analysis included four transplanted patients aged 66-70 years and Mazza et al 18 recently reported PBSCT in five NHL patients Ͼ65 years of age (67-76 years). While it may be concluded that PBSCT may be feasible in selected NHL patients aged up to 65 years, very limited published experience is available on this approach in NHL patients over 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Stamatoullas et al 16 transplanted two patients older than 65 years. Our analysis included four transplanted patients aged 66-70 years and Mazza et al 18 recently reported PBSCT in five NHL patients Ͼ65 years of age (67-76 years). While it may be concluded that PBSCT may be feasible in selected NHL patients aged up to 65 years, very limited published experience is available on this approach in NHL patients over 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Median duration of neutropenia (ANC Ͻ0.1 ϫ 10 9 /l) was 6 days (range: 2-18); the ANC remained below 0.5 ϫ 10 9 /l for a median time of 8 days (range: [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in all transplant procedures.…”
Section: Hematological Toxicity and Engraftment Kineticsmentioning
confidence: 99%
“…An EBMT survey reports transplant-related mortality 13% (TRM) in patients aged 55 years and over, transplanted for intermediate-high grade NHL, 10 but more recent data suggest that in the same setting, very low TRM can be achieved, using mobilized PBSC and conditioning regimens not including TBI. [7][8][9] Here, we report our single center experience in 48 patients aged Ͼ60 years (33% of these aged Ͼ65 years), autotransplanted with PBSC for hematological malignancies. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Feasibility of this procedure in patients older than age 60 years has been demonstrated by a number of smaller reports investigating patients between the ages of 61-76 years, 34 61-68 years 35 and 61-65 years, 36 undergoing autologous stem cell transplant predominantly for multiple myeloma and nonHodgkin lymphoma (NHL). An acceptable TRM within the first 100 days of between 0 and 17% was noted in these elderly patient studies.…”
Section: Autologous Stem Cell Transplantation: Generalmentioning
confidence: 99%